The primary school as a therapeutic community - MacDonald, Shelley; Winship, Gary (Emerald, 2016)
Purpose – The purpose of this paper is to consider the changes underway in the delivery of services to children and young people in schools, not least that OFTSED will soon be routinely carrying out an assessment of mental health provision in schools. This paper considers the policy context to these changes and the recent initiatives that are informing the evolution of initial teacher training. Alongside the changes in Child and Adolescent Mental Health Services there are an increasing number of schools developing counselling and psychotherapy services. How can the School counsellor look to develop a who school as therapeutic community. Design/methodology/approach – A case narrative is presented of a seven-year-old child who was referred to the school counselling service. The narrative draws attention to the array of dynamic interactions, from peers to teachers to parents which the school counselling manager encountered. Findings – It is argued that it is necessary for the school counsellor to have a framework for understanding how all parts of the school work together and it is proposed that we might usefully consider the primary school as a therapeutic community. Originality/value – There are a raft of policy changes and practices in recent years that have altered the landscape of early intervention and the mental health agenda in primary schools. This paper captures this debates and consider how therapeutic community ideology is positioned as an opportunity to think more expansively about mental health in primary schools